Synthesis, Characterization and Antimicrobial Evaluation of Mannich Bases of 4-(Furan-2-yl-methyleneamino)-3-(2-hydroxyphenyl)-1H-1,2,4-triazole-5-thione - Deo, Prem Shankar; Rawat, Rhambus; Shakya, Bhushan (Journal of Nepal Chemical Society, 2021)
Triazole nucleus has drawn much attention since the last decade because of its various potent biological activities. The pharmacological application of triazoles has been widely recognized and well documented. Schiff and Mannich bases are both considered as bioactive compounds, however, there are not much of documentation about the Mannich bases as their study has begun lately. The main aim of this study was to synthesize new Mannich bases from Schiff base bearing 1,2,4-triazole nucleus to access their antimicrobial activities. The newly synthesized compounds 1,2,4-triazole-5-thione, Schiff base (4) and Mannich bases (5a & 5b) were characterized by spectral techniques like UV, FT-IR, and NMR. Mannich bases were tested against various bacterial (gm +ve and gm –ve) as well as fungal strains. The synthesized Mannich bases showed good to moderate activities against the tested bacterial and fungal strains.